ADHD in Early Childhood: Part 1 - Understanding ADHD in Preschoolers - Allie Munch; Heidi Liss Radunovich (EDIS, 2012)
Attention-Deficit/Hyperactivity Disorder (ADHD) is a brain-based disorder that involves difficulty with paying attention, staying still, and thinking carefully about things ahead of time. Preschool children with ADHD are a lot more hyperactive, impulsive, and inattentive than children who do not have ADHD. This 3-page fact sheet was written by Allie Munch and Heidi Liss Radunovich, and published by the UF Department of Family, Youth and Community Sciences, July 2012.